Effect of different nitrogen fertilizer treatments on the conversion of Miscanthus × giganteus to ethanol. (November 2017) - Dubis, Bogdan; Bułkowska, Katarzyna; Lewandowska, Małgorzata; Szempliński, Władysław; Jankowski, Krzysztof Józef; Idźkowski, Jakub; Kordala, Natalia; Szymańska, Karolina
Highlights: Fertilization influences biomass yield and content of lignocellulosic fractions. Bioethanol production was highest with hydrolysis and fermentation done separately. Sewage sludge or NPK fertilizer increased ethanol production 30 or 40%, respectively. Abstract: Miscanthus  ×  giganteus is a perennial rhizomatous grass which is used as a biofuel crop. Due to its high yields, low production costs, resistance to low temperatures, low soil requirements and, above all, high cellulose content, miscanthus can be a useful resource for ethanol production. The aim of this study was to determine the effect of two fertilization regimes (sewage sludge/mineral NPK) during miscanthus cultivation on the chemical composition of biomass, the content of major lignocellulosic factions and the effectiveness of miscanthus conversion to bioethanol. The results indicate that fertilization treatments influenced biomass yield and the content of major lignocellulosic fractions. Bioethanol production was higher when hydrolysis and fermentation processes were conducted separately than when saccharification and fermentation were conducted simultaneously. Ethanol production increased by 30% and 40% in response to sewage sludge and NPK (equivalent nitrogen content = 160 kg N/ha) fertilization, respectively, in comparison with unfertilized crops.